Glyphosate adsorption onto porous clay heterostructure (PCH): kinetic and thermodynamic studies - Besghaier, Sabrine; Cecilia-Buenestado, Juan Antonio; Chouikhi, Nesrine; Vilarrasa García, Enrique; Rodríguez-Castellón, Enrique; Chlendi, Mohamed; Bagane, Mohamed (Springer, 2021)
The synthesis of PCH from natural bentonite produces a porous heterostructure material effective for the adsorption of glyphosate from water. The adsorption process takes place through an interaction between the silanol group of montmorillonite and/or the PCH adsorbent with the functional groups of glyphosate. The glyphosate adsorption isotherms, recorded for all the studied samples, have been established to be of Langmuir type. The kinetic of the herbicide adsorption on the PCH was best described by the pseudo-second-order model. With the increase in temperature from 25 to 50 °C, the sorption capacities of the materials studied towards glyphosate increased. The process of glyphosate adsorption was found to be endothermic and spontaneous in nature, as indicated by positive values of ΔH and negative values of ΔG. According to the results obtained, the herbicide sorption was more effective in a basic environment. The maximum amount of adsorbed glyphosate is almost doubled with PCH from 13.5 mg/g of natural clay to 27.5 mg/g of PCH.
Keywords: Glifosato; Porous clay heterostructures; PCH; Glyphosate; Adsorption; Organophosphate